Visually Optimized Two-Pass Rate Control for Video Coding Using the Low-Complexity XPSNR Model - Helmrich, Christian R.; Zupancic, Ivan; Brandenburg, Jens; George, Valeri; Wieckowski, Adam; Bross, Benjamin (Visual communications and image processing (Online), 2021)
Two-pass rate control (RC) schemes have proven useful for generating low-bitrate video-on-demand or streaming catalogs. Visually optimized encoding particularly using latest-generation coding standards like Versatile Video Coding (VVC), however, is still a subject of intensive study. This paper describes the two-pass RC method integrated into version 1 of VVenC, an open VVC encoding software. The RC design is based on a novel two-step rate-quantization parameter (R-QP) model to derive the second-pass coding parameters, and it uses the low-complexity XPSNR visual distortion measure to provide numerically as well as visually stable, perceptually R-D optimized encoding results. Random-access evaluation experiments confirm the improved objective as well as subjective performance of our RC solution.